2020
DOI: 10.1097/inf.0000000000002849
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Double-blind, Placebo-controlled Trial of Saccharomyces boulardii in Infants and Children With Acute Diarrhea

Abstract: Aim: This study was designed to assess the efficacy and safety of Saccharomyces cerevisiae variant boulardii CNCM I-3799 ( S . boulardii CNCM I-3799) in the management of acute diarrhea in children. Methods: A total of 100 infants and children 3–36 months of age with acute diarrhea received medical care according to the World Health Organization guidelines on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Previous studies of probiotics in the treatment of diarrhea have mostly focused on acute diarrhea, viral diarrhea or AAD, and many have confirmed the effectiveness of probiotics for diarrhea symptoms in these cases (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of probiotics in the treatment of diarrhea have mostly focused on acute diarrhea, viral diarrhea or AAD, and many have confirmed the effectiveness of probiotics for diarrhea symptoms in these cases (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Huang et al (18) have shown that bacterial probiotic therapy shortens the duration of acute diarrheal illness in children. Mourey et al (19) have shown that probiotics in children with acute diarrhea were shown effective in decreasing the severity and duration of diarrhea in children.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve articles (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) with 744 patients were included in the current meta-analysis and were published between 2010 and 2020. Three studies (12,15,17) used combined probiotics for the treatment method, with 2-5 collective probiotic species.…”
Section: Basic Characteristics Of the Included Rctsmentioning
confidence: 99%
“…Six articles (8,9,11,13,18,19) reported changes in diarrhea in children 2 days after the treatment intervention, and the 2-day treatment efficacy rate for diarrhea in the probiotics group was greater than in the control group (OR =2.12, 95% CI: 1.47-3.05, Z=3.998, P=0.000). Statistical heterogeneity was evident between the articles (I 2 =46.6%, P=0.096) (Figure 3).…”
Section: The 2-day Treatment Efficacy Rate For Diarrhea (%)mentioning
confidence: 99%